2022
DOI: 10.7759/cureus.22936
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Presentation of Infective Endocarditis Due to Serratia marcescens

Abstract: Serratia marcescens is an opportunistic organism that can commonly cause respiratory tract infections in immunocompromised individuals. It has also been shown to cause urinary tract infections and soft tissue infections. It has several virulence factors including fimbriae-like adhesions that allow for surface attachment and biofilm formation to increase the likelihood of infections in humans. However, it has rarely been shown to cause infective endocarditis but has an increased mortality compared to the usual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Case reports have described Serratia endocarditis and its sequelae in the form of valvular abscess formation, embolic phenomena, aorto-atrial fistula formation, ventricular septal defects, septic arthritis, and meningitis [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Case reports have described Serratia endocarditis and its sequelae in the form of valvular abscess formation, embolic phenomena, aorto-atrial fistula formation, ventricular septal defects, septic arthritis, and meningitis [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lafuente Martinez et al (15,18) Male, 17 years old Knee Intraarticular injection Amikacin Watanakunakorn (8) Female, 69 years old Sternoclavicular Subclavian catheter Ceftizoxime + gentamycin Svensson et al (22) Male, 46 years old Male, 40 years old Hip, ankle Diabetes + UTI postoperative infection TMP-SMX + cefotaxime ceftazidime Greene (23) Male, 16 years old Ankle Foreign body remnants (splinter) Cefotaxime Nakashima et al (13) 8 cases Knee, shoulder Epidemic due to contaminated benzalkonium chloride -Carmichael (24) Male, 15 months old Vertebra Broviac catheterization Ceftriaxone Chiu and Wang (6) Male, 34 years old Knee Traffic accident, contaminated wound Trimethoprim and Sulfamethoxazole Hadid et al (16) Male, 72 years old Ankle Minor trauma contaminated with soil Ertapenem Sandal et al (18) Male, 10 weeks old Knee Escobar syndrome Meropenem Shah et al (19) Male, 50 years old Infective endocarditis…”
Section: Case Affected Joint Source Treatmentmentioning
confidence: 99%
“…Treatment consisted of intravenous meropenem. Shah et al reported a rare presentation of infective endocarditis due to Serratia marcescens (19) . The patient had a rapid onset of complications, including joint infections, splenic abscesses, myositis, and septic arthritis, despite an initial benign presentation of pneumonia.…”
Section: Ivdu Meropenemmentioning
confidence: 99%